EFFECT OF BIOFERTILIZER TRICHODERMA HARZIANUM T-22 APPLICATION, GROWING MEDIUM AND TRAINING METHODS ON SOME CHARARCTRESTICS FOR LANTANA CAMARA PLANTS - afnan yahya; muhammad Al-Sawaf; .nidal almura (Mesopotamia Journal of Agriculture)
An experiment was in the green net canopy Department of Horticulture and Landscape College of Agriculture and Forestry / University of Mosul from May 2019 to October 2019, to investigate the effect of Trichoderma harzianum T-22 application and three growing media (soil, 1:3 soil: peatmoss, 1:1 soil: peatmoss) and three pruning training method (1, 4, 6 branches) and their interaction on the vegetative and flowering growth of Lantana camara. Results showed that T. harzianum application, the growing medium, pruning training method and their interaction had significant effects on the vegetative and flowering growth of plant. The highest average of plant height, stem diameter, leaves number, chlorophyll content and flowering date gives in T. harzianum which increases plant height which was 52.31 cm, stem diameter 8.06 cm, leaves number 164.65, chlorophyll content 25.98 SPAD and flowering date 85.84 day. Results have shown that pruning training Lantana plants on six branchesgave the highest average for plant height 52.29 cm, chlorophyll content 38.69 SPAD and flowering date 79.25 day. Growing medium 1:1 soil:peat moss gives the highest average for plant height 51.97 cm, stem diameter 8.28 cm, chlorophyll content 26.29 SPAD and flowering date 93.33 day.